COMPARATIVE EDUCATION AND QUALITY OF TEACHING: AN ANALYSIS OF THE EDUCATIONAL PERFORMANCE OF PIAUÍ IN A NATIONAL PERSPECTIVE - da Cunha Santiago, Izael; Aparecida Guerino Ragonezi, Helaing; Luciene Rocha Gomes, Martha; da Cunha Santiago, Iraneide (Revista Gênero e Interdisciplinaridade, 2026)
This study analyzes the quality of education in the state of Piauí in comparison with the broader Brazilian educational context, integrating quantitative indicators, public policies, and the perspectives of administrators, teachers, and students. Using a multi-method approach—including document analysis, semi-structured interviews, field observations, and the review of official educational data—the research seeks to understand how progress and challenges emerge within state and municipal systems. The findings indicate that, in the early years of Elementary Education, Piauí has achieved notable gains due to the influence of PPAIC, continuous training across different regions, and the enhanced use of diagnostic assessment. However, structural disparities in learning remain evident, particularly in the final years of schooling and in the upper grades, with significant gaps recorded in Portuguese Language and Mathematics. Inadequate infrastructure, shortage of qualified teachers, high staff turnover, and differences between urban and rural environments—among other factors—continue to hinder the consolidation of high-quality education. Students’ perceptions underscore the need for equitable policies that align access, retention, and pedagogical practices with local realities. Comparative analyses show that, although Piauí has reduced some historical inequalities, its proficiency levels and school continuity rates remain well below national averages. Therefore, the study argues that educational progress in the state depends on sustaining localized policies, strengthening teacher training, improving pedagogical management, and investing in infrastructure that reflects regional needs.